An Analysis of Islamic Business Ethics Among Muslim Business Actors in the Shopee Marketplace in Palangka Raya - Sukti, Surya; Alfia, Siti (Fakultas Ekonomi Universitas Kadiri, 2025)
The development of digital technology has brought significant changes to the trading system, including the emergence of marketplaces such as Shopee, which is widely utilized by Muslim businesses in Palangka Raya City. This ethics study aims to analyze how Islamic business values are applied in online buying and selling practices by these businesses. The study used a descriptive qualitative approach using observation and in-depth interviews with active Muslim sellers on Shopee. The data were analyzed through stages of reduction, presentation, and drawing conclusions based on Islamic ethical principles such as the prohibition of usury (riba), the avoidance of gharar (unlawful activity), and the application of justice, honesty, and benefits (maslahat). The results show that Muslim businesses generally strive to maintain their business activities in accordance with sharia. In terms of transactions, most avoid interest-bearing loans and choose cash payment methods, Islamic bank transfers, or cash on delivery (COD) to reduce the possibility of usury. Clarity of product descriptions and price transparency are maintained to avoid gharar (unlawful activity), while speculative promotions such as sweepstakes or